Epilepsy: Workup and Management in Adults - O'Dwyer, Rebecca (Seminars in Neurology, 2020)
When managing epilepsy, there is a temptation to focus care with respect to the last and the next seizure. However, epilepsy is a multifaceted chronic condition and should be treated as such. Epilepsy comes with many physical risks, psychological effects, and socioeconomic ramifications, demanding a long-term commitment from the treating physician. Patients with epilepsy, compared to other chronically ill patient populations, have a worse quality of life, family function, and less social support. The majority of patients are well controlled on antiseizure drugs. However, approximately one-third will continue to have seizures despite optimized medical management. The primary aim of this article is to explore the long-term management of chronic epilepsy, and to address some of the particular needs of patients with chronic epilepsy.
Keywords: epilepsy; medical management; breakthrough seizures; women with epilepsy; older adults